Tilt Detection Of Connectors Using Phase Shifting. - Retnasamy, V; Ratnam, Mani Maran; Sundaraj, K; Sauli, Zaliman (2007)
AVI’s are playing important roles in quality inspection in the electronic industry. Most existing AVIs are single overhead camera and are incapable detecting 3D defects. This work presents solving the shortcoming stated using an angle fringe projection.